Red Blood Cell-Derived Extracellular Vesicles Display Endogenous Antiviral Effects and Enhance the Efficacy of Antiviral Oligonucleotide Therapy - Jayasinghe, Migara K (AMER CHEMICAL SOC, 2024)
10.1021/acsnano.3c06803